An effective hybrid goal programming approach for multi-objective straight assembly line balancing problem with stochastic parameters - Mardani-Fard, Heydar Ali; Hadi-Vencheh, Abdollah; Mahmoodirad, Ali; Niroomand, Sadegh (Operational research, 2020)
A new multi-objective straight assembly line balancing problem is focused in this study. The problem happens in a stochastic environment where the task times and the task performing quality levels are distributed normally. The objectives like equipment purchasing cost, worker time dependent wage, and average task performing quality of the assembly line are to be optimized simultaneously. A mixed integer non-linear formulation is proposed for the problem. Applying a chance-constrained modeling approach and some linearization techniques the model is converted to a crisp multi-objective mixed integer linear formulation. To tackle such problem, a hybrid fuzzy programming approach is proposed and combined with a typical goal programming method to construct a new hybrid goal programming approach. The computational experiments of the study results in a superior performance of the proposed approach comparing to the literature.